2002
DOI: 10.1002/ppul.10108
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of dexamethasone and hydrocortisone on alveolar growth in rat pups

Abstract: Glucocorticoids are widely used in perinatology, since they decrease the incidence of respiratory distress syndrome and chronic lung disease. However, evidence is now increasing that their use in this age group may result in impaired alveolar lung growth and general development. The aim of this study was to determine whether a low dose of hydrocortisone (1 mg/kg/day for 11 days) was deleterious to lung growth in rat pups, as compared to an equivalent dose of dexamethasone. While both dexamethasone and hydrocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…However, even though DXM or HCS reduced pulmonary inflammation in our study, that did not protect the lungs from their negative effects in terms of alveolar growth. Fayon et al (19) compared the effect of DXM and HCS on lung growth with a lower DXM dose than we used, and they also found that alveolarization was more markedly impaired by DXM than HCS. Dik et al (30) demonstrated that DXM treatment increased fibroblast proliferation despite apparent down-regulation of inflammation in preterm infants at risk of BPD.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, even though DXM or HCS reduced pulmonary inflammation in our study, that did not protect the lungs from their negative effects in terms of alveolar growth. Fayon et al (19) compared the effect of DXM and HCS on lung growth with a lower DXM dose than we used, and they also found that alveolarization was more markedly impaired by DXM than HCS. Dik et al (30) demonstrated that DXM treatment increased fibroblast proliferation despite apparent down-regulation of inflammation in preterm infants at risk of BPD.…”
Section: Discussionmentioning
confidence: 58%
“…These findings were not in agreement with those reported in rats with no other risk factors for altered lung growth. Thus, Fayon et al (19) found that in rat pups with no risk factors for BPD, both HCS and DXM increased alveolar diameter, and decreased the thickness of the inter-airspace walls. This thinning of the inter-airspace walls due to precocious maturation prior to alveolarization was more marked with DXM than HCS.…”
Section: Discussionmentioning
confidence: 99%
“…However, high or repeated doses can inhibit postnatal somatic and lung growth (253). During the period of active postnatal alveolarization in rats, glucocorticoids inhibit secondary crest formation, accelerate alveolar wall thinning, decrease alveolar number and surface area (20,(254)(255)(256)(257), diminish replication of fibroblasts, impair the conversion of types II to I pneumocytes (255,258,259), and alter collagen and elastin deposition (149,254,260,261), resulting in a morphologic appearance resembling emphysema. In ferrets, corticosteroid treatment reduces size-corrected airway conductance, suggesting that the central airways are more sensitive to its effect than lung parenchyma (262).…”
Section: Nonmechanical Signals and Mediatorsmentioning
confidence: 99%
“…In the present study, the number of alveolar attachments was significantly reduced in both the Bud-and Dex-treated animals; however, this was only the case for airways with a Pi Ͻ 0.75 mm. Similarly, a recent study by Fayon and colleagues (9) reported that the number of alveolar attachments to bronchioles per millimeter of the peribronchial sheath (diameter Ͻ 0.4 mm) was reduced by one-third in Dex-treated rat pups (0.4 g subcutaneous daily between days 4 and 14) compared with controls and hydrocortisone-treated animals. These findings also illustrate the varied effects of different types of glucocorticoids, and it is likely that this variability is dependent on the drug delivery method, dose, and potency.…”
Section: Discussionmentioning
confidence: 66%